2019
DOI: 10.1159/000496640
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of Intravenous Iron Administration and Iron-Containing Phosphate Binders on Serum Intact Fibroblast Growth Factor 23 Levels

Abstract: Aims: This study assessed the impact of iron administration on serum fibroblast growth factor 23 (FGF23) levels. Methods: Of 123 hemodialysis (HD) patients treated with erythropoiesis-stimulating agents, 22 received once-weekly intravenous iron and 17 received daily oral iron with iron-containing phosphate binders. Intact FGF23 and biomarkers of iron metabolism were measured from blood samples drawn before each HD session, at baseline and on days 3, 5, 7, and 14. Results: Phosphate levels did not differ among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, a stronger association was identified between acute reactions and the risk of infectious disease in patients being treated with intravenous iron than that in those being treated with oral iron [30]. Furthermore, it has been reported that intravenous iron administration increases the circulating FGF23 concentration, whereas oral iron reduces FGF23 in these patients [15,32]. Therefore, oral iron is used in preference in our hospital and only one patient had received intravenous iron supplementation at baseline in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…However, a stronger association was identified between acute reactions and the risk of infectious disease in patients being treated with intravenous iron than that in those being treated with oral iron [30]. Furthermore, it has been reported that intravenous iron administration increases the circulating FGF23 concentration, whereas oral iron reduces FGF23 in these patients [15,32]. Therefore, oral iron is used in preference in our hospital and only one patient had received intravenous iron supplementation at baseline in the present study.…”
Section: Discussionmentioning
confidence: 65%
“…The ExplorIRON-CKD trial is the first exploratory comparative trial including two modern intravenous irons, FCM and FDI, in the ND-CKD population studying a potential hypophosphatemic effect. Previous studies in patients with ND-CKD and on hemodialysis incorporating oral and intravenous iron have had contradictory results [20‒25, 41, 51, 52], especially in terms of FGF-23 metabolism, where the changes in FGF-23 did not necessarily translate to clinically significant hypophosphatemia even when a decrease in phosphate was seen. The measure of iFGF-23 as opposed to cFGF-23 can provide further information on the action of bioactive FGF-23 in relation to any effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic kidney disease represents a state of increased FGF-23 concentration, which potentially is key in the development of CKD mineral bone disorder [19]. The exact nature of alterations in metabolism of FGF-23 in CKD is poorly understood, and therefore it is difficult to explain the discrepancies that exist between FGF-23 concentrations (iFGF-23 and cFGF-23) following intravenous iron administration in hemodialysis-dependent patients [20][21][22][23][24]. Nonetheless, a key study (n = 65) prospectively examined the effects of 1,000 mg of FCM on FGF-23 in patients with normal renal function, pregnant individuals, and patients with ND-CKD [25].…”
Section: Introductionmentioning
confidence: 99%